Studi Efektivitas Ketorolak Versus Metamizol Untuk Nyeri Paska Operasi Transurethral Resection Of The Prostate (TURP) - Ita Octafia; Riza Mazidu Sholihin; Yosi Irawati Wibowo; Adji Prayitno Setiadi (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2024)
Limited evidence was available on the use of analgesic post-transurethral resection among patients with Benign Prostate Hyperplasia (BPH). This research was conducted at dr. Harjono Ponorogo Regional Public Hospital in September – November 2021. A total of 90 patients with BPH was randomly assigned to receive Ketorolac injection 30 mg (n=45) and Metamizole 1000 mg injection (n=45) post-TURP. Numeric Rating Scale (NRS) was used to measure the level of pain before surgery (T0); and 30 minutes (T1), 1 hour (T2), 2 hours (T3), 4 (T4) and 6 hours (T5) after surgery. In addition, haemoglobin (Hb) values and adverse events were observed. Inferential statistical tests were used to analyze differences between the two groups. The level of pain in the Metamizole group was lower than Ketorolac group at T1 and T2 (2.71 versus 2.18, p=0.001; and 2.51 versus 2.11, p=0.000; respectively). The AUC values between the two groups showed a statistical difference (p=0.02). The Hb values pre- and post-TURP were significantly different in Metamizole as well as Ketorolac groups (all p=0.001), but there was no difference between groups. This finding indicates that Metamizole injection can be considered as an alternative  for post-TURP analgesic with better availability and lower cost